(untitled) (Jurnal Akuntansi dan Keuangan, 2013)
The purpose of this study is to investigate the effect of ownership structure on profitability in the manufacturing sector. Independent variables used for this study are consisted of foreign ownership, government ownership, managerial ownership, institusional ownership, family ownership. Profitability is measured by ROA (Return On Assets), while firm size and leverage are used as the control variables. This study is used 224 samples of manufacturing companies listed in Indonesian Stock Exchange for the period 2010-2011. The results show that foreign ownership and leverage have a positive and significant effect to profitability. Family ownership has a negative and significant effect to profitability. However, government ownership, managerial ownership, institutional ownership and firm size have no influence to profitability.